Multifocal Atrial Tachycardia in a 9-Month-Old Infant: A Case Report with Therapeutic Insights - Diego Chemello; Camila Sales Fagundes; Patricia Chagas; Leticia Hadlich Correa de Barros; Patricia Rodrigues Lemos Cardoso (Jurnal Kardiologi Indonesia, 2026)
Background: Supraventricular tachycardia is the most common arrhythmia in infants, with an estimated prevalence between 1/250 and 1/1000. Multifocal Atrial tTachycardia (MAT), a rare subtype accounting for less than 1% of supraventricular tachycardia in infants and children, is characterized by multiple atrial foci, variable P-wave morphologies, and irregular ventricular response. When incessant, MAT may lead to tachycardia-induced cardiomyopathy and congestive heart failure. This report describes a 9-month-old infant with MAT and left ventricular dysfunction, emphasizing diagnostic challenges and therapeutic strategies Case Illustration: A previously healthy 9-month-old female infant presented for urgent evaluation due to progressive dyspnea and tiredness during breastfeeding, which had begun approximately two months earlier and worsened in the last two weeks. Her mother noted perioral cyanosis during crying and feeding. On examination, she was tachypneic (60 breaths/min), tachycardic (180 bpm), and mildly dehydrated. Transthoracic echocardiography revealed a dilated left ventricle with moderate systolic dysfunction (ejection fraction 35%). A 12-lead electrocardiogram demonstrated multifocal atrial tachycardia with at least three distinct P-wave morphologies and irregular R-R intervals, and Holter monitoring confirmed an incessant pattern (>30% of the day). Three synchronized direct current cardioversion attempts (0.5, 1.0, and 1.23 J/kg) failed to restore sinus rhythm. Intravenous amiodarone was initiated (loading dose 5 mg/kg over 1 hour, followed by 10 mcg/kg/min), later transitioned to oral therapy (5 mg/kg/day). Within 48 hours, sinus rhythm was restored, heart failure symptoms resolved, and follow-up echocardiography showed improved ejection fraction (55%). Propranolol (1 mg/kg/day) and digoxin (5 mcg/kg/day) were added for rate control. The patient was discharged asymptomatic after one week, with no relapse at 6-month follow-up. Conclusions: MAT is a rare cause of supraventricular tachycardia in infants and may be present with congestive heart failure due to tachycardia-induced cardiomyopathy. Incessant forms are typically defined by an arrhythmia burden greater than 30% of the day on Holter monitoring. Failure of direct current cardioversion is a hallmark of MAT, reinforcing the role of pharmacological management. Early recognition and rate and rhythm control with agents such as amiodarone, propranolol, and digoxin can lead to rapid recovery of left ventricular function and an excellent prognosis in infants without structural heart disease.